(untitled) (Islamic Sciences Journal, 2023)
Islamic law is able to deal with all new things, keep pace with the requirements of the times, and find a juristic rule for all the coming down or all the developments of life, and examples of this are what we discussed among the pages of this research, and we found that intelligence is valid using modern machines, as the slaughtering of the scruff is valid under the conditions we mentioned during Research, and that the noun is divided if the pronouncer uttered it when operating the mechanical slaughtering machine, as we have known the mercy of the Sharia of the animal in its permissibility to anesthetize it before slaughtering it in order to reduce the pain on it. Walks of life, finding a The provisions of its own legitimacy.